Analisis Persepsi Guru PAI terhadap Perubahan Kurikulum PAI dari Masa ke Masa di Sumatera Barat: Implikasi untuk Pengembangan Kebijakan - Khairunnisa, Khairunnisa; Sesmiarni, Zulfani (ALSYS, 2025)
Curriculum transformation in the digital revolution era demands rapid adaptation from educators, including teachers of Islamic Religious Education (Pendidikan Agama Islam, PAI). In this context, it is essential to understand teachers' perceptions of the new curriculum dynamics and the challenges associated with its implementation. This study aims to explore the perspectives of PAI teachers in West Sumatra regarding curriculum changes and to identify barriers to integrating technology and artificial intelligence (AI) into the learning process. A quantitative approach was employed, with data collected through a structured questionnaire. The results show that over 76% of PAI teachers hold a positive attitude toward curriculum changes. However, they face several implementation challenges, including limited training in technology, restricted access to digital learning resources, and a lack of institutional support. These findings underscore the need for a more holistic curriculum development strategy, which includes strengthening educators’ capacities through continuous professional training and the provision of adequate supporting infrastructure. This study offers valuable insights for policymakers and educational institutions in designing an adaptive PAI curriculum aligned with the demands of the digital age.